2017
DOI: 10.1089/ast.2016.1599
|View full text |Cite
|
Sign up to set email alerts
|

Methane: Fuel or Exhaust at the Emergence of Life?

Abstract: As many of the methanogens first encountered at hydrothermal vents were thermophilic to hyperthermophilic and comprised one of the lower roots of the evolutionary tree, it has been assumed that methanogenesis was one of the earliest, if not the earliest, pathway to life. It being well known that hydrothermal springs associated with serpentinization also bore abiotic methane, it had been further assumed that emergent biochemistry merely adopted and quickened this supposed serpentinization reaction. Yet, recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 182 publications
3
60
0
Order By: Relevance
“…And we alert the reader to a significant revision of the AHV theory since its first proposal, namely that although we still recognize that the job of life overall is to hydrogenate carbon dioxide, it may be that life first captured both the partially and fully reduced forms of C1 carbon as hydrothermal formate and methane, and only later (though well before LUCA) 'learnt' to reduce CO2 through all the required intermediates for CO2 autotrophy to emerge from its mineral placenta. [50, 54,55] At bottom is the assumption that the protonically and electronically powered nanoengines and disequilibrium conversions needed to drive those endergonic reactions required to produce life's many processors and its superstructures today were initially coopted from iron oxyhydroxides and sulfides, dosed with transition metals and phosphate, precipitated at the submarine alkaline vent. [13,280,281,282] However, even in the light of some experimental support we can see no clear path to the nucleotide world and, beyond intriguing suggestions of Greenwell and Coveney and others, the theory dissipates in hypotheses, ideas and speculation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And we alert the reader to a significant revision of the AHV theory since its first proposal, namely that although we still recognize that the job of life overall is to hydrogenate carbon dioxide, it may be that life first captured both the partially and fully reduced forms of C1 carbon as hydrothermal formate and methane, and only later (though well before LUCA) 'learnt' to reduce CO2 through all the required intermediates for CO2 autotrophy to emerge from its mineral placenta. [50, 54,55] At bottom is the assumption that the protonically and electronically powered nanoengines and disequilibrium conversions needed to drive those endergonic reactions required to produce life's many processors and its superstructures today were initially coopted from iron oxyhydroxides and sulfides, dosed with transition metals and phosphate, precipitated at the submarine alkaline vent. [13,280,281,282] However, even in the light of some experimental support we can see no clear path to the nucleotide world and, beyond intriguing suggestions of Greenwell and Coveney and others, the theory dissipates in hypotheses, ideas and speculation.…”
Section: Discussionmentioning
confidence: 99%
“…But showing how selection for the 'fittest' in this sense can happen, or does happen, in the mineral precipitates is the major challenge? [3,4,55,177] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current understanding of methanogenesis evolution is that ancestors of the Euryarchaeota phylum were methanogens (Evans et al , 2019), or potentially methanotrophs or alkanotrophs (Spang et al , 2017), with methanotrophy-driven acetogenesis also being proposed as an early metabolism type (Russell and Nitschke, 2017). It has been suggested that some euryarchaeal lineages, such as the Thermoplasmatales , lost the methanogenesis pathway, while others, such as the Methanomassiliicoccales , retained at least part of the pathway (Evans et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, in extreme (e.g. ice and permafrost) environments at ∼ 230 K, the turnover time is predicted to be several orders of magnitude higher(Price and Sowers, 2004).19 In this regard, we caution the reader that it is not yet clear as to whether methane may have served as the energy source or a byproduct of early life(Russell and Nitschke, 2017), and the existence of either methanogens or methanotrophs on subsurface worlds is not guaranteed.…”
mentioning
confidence: 99%